Smak och konsistens hos ost : en litteraturstudie kring årstiderna och fodrets inverkan - Valentin, Louise (SLU/Dept. of Food Science, 2011)
To enjoy the richness of the grazing cows and high yield during the summers, even during the winter, cheese has been the way to store milk for thousands of years. Nowadays yield is high all year around and the cheese production is possible during all seasons. The aim of this paper is to investi-gate how and why the seasons influence taste and texture of pressed and ripened cheese. Milk is composed of proteins, fat, lactose and water but contains also a lot of vitamins. The quality of milk is very important for the final constitution of cheese. The processing of milk to produce enzymatic clotted cheese is briefly as follows: addition of starter culture, clotting by adding rennet, cutting of the gel, heating, stirring, shaping, compressing, salting and ripening. The steps are performed in different ways depending of which type of cheese that is produced. When producing hard cheese, all steps are performed in order to promote the syneresis. While in the production of softer types of cheeses it is important to make sure that a greater part of the water stays in the cheese gel. During ripening the taste of the cheese develops, by degradation of fat and proteins. Moreover, bacteria synthesize some vitamins during ripening; this is why cheese may contain water-soluble vitamins even though all water-soluble vitamins are deleted with the whey. To facilitate the cheese making process and make cheese yield more equal over the seasons, the quota of protein and fat content is standardized. In some cases the quotas of caseins and whey proteins are standardized as well, since the amount of caseins is decreasing during the summer that contribute to a lower cheese yield. Other factors that also influence the taste of the cheese, such as the plasmin activity, are not regulated. The plasmin activity increases during grazing and its role during ripening is to degrade proteins. The plasmin activity has a great influence of the cheese taste and texture. Furthermore, the length of the fatty acids in the milk is influenced by the feed and is not standardized. The milk of grazing cows has a higher amount of longer fatty acids including the healthy CLA fatty acid. There is also a link between season and the quantity of vitamin A in the milk. Vitamin A is also found in the cheese when it is fatsoluble.